SLOWLY ROTATING WORMHOLE SOLUTION - Anuar Alias et al. (Proceedings of ICMSA, 2005)
The ideas introduced by Einstein General Relativity theory toward thedevelopment of wormhole research field are reviewed namely, theconcept of spacetime, Riemarxrian geometry, cosmological constantand the pioneering work of Einstein and Rosen on the subject.Spherically symmetric spacetime metric that provides the wormholespacetime metric by the revival works of Morris and Thorne arediscussed. Concerning recent works on the subject a generalizedwormhole solution with cosmological constant introduced by the worksof Lemos, Lobo and Oliveira are also discussed. Finally, the rotatingwormhole solution as introduced by Khatsynovsky and Teo hasprovided a more generalized solution compared with the Morris-Thornestafic solution. Based on these ideas, we proposed the spacetime metricof a slowly rotating spherically s)rynmetric wormhole where weconstructed set ofEinstein equalions in term ofpressure and the energydensity of the wormhole.Keywords; General Relatfuity; Cosmological constant; Einstein-RosenBridge; Wormhole